2016
DOI: 10.1364/oe.24.007495
|View full text |Cite
|
Sign up to set email alerts
|

Controllable circular Airy beams via dynamic linear potential

Abstract: We investigate controllable spatial modulation of circular autofocusing Airy beams, under action of different dynamic linear potentials, both theoretically and numerically. We introduce a novel treatment method in which the circular Airy beam is represented as a superposition of narrow azimuthally-modulated one-dimensional Airy beams that can be analytically treated. The dynamic linear potentials are appropriately designed, so that the autofocusing effect can either be weakened or even eliminated when the line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…It has been shown that the propagation trajectory as well as the positions of autofocusing points of the AAF beams can be controlled by potentials [41]. In our investigation [80], we theoretically analyzed the propagation and autofocusing effect of the AAF beams in a dynamic linear potential. We found that the linear potential may weaken (even eliminate) or strengthen the For the case with d(z) = 13 − 12z, from the corresponding trajectory x p = r 0 − z 3 + 3z 2 , we know that the beam will undergo autofocusing during propagation, so the process should be described by Equation (43).…”
Section: Dynamic Linear Potential Guidancementioning
confidence: 99%
“…It has been shown that the propagation trajectory as well as the positions of autofocusing points of the AAF beams can be controlled by potentials [41]. In our investigation [80], we theoretically analyzed the propagation and autofocusing effect of the AAF beams in a dynamic linear potential. We found that the linear potential may weaken (even eliminate) or strengthen the For the case with d(z) = 13 − 12z, from the corresponding trajectory x p = r 0 − z 3 + 3z 2 , we know that the beam will undergo autofocusing during propagation, so the process should be described by Equation (43).…”
Section: Dynamic Linear Potential Guidancementioning
confidence: 99%
“…It has been shown that the propagation trajectory as well as the positions of autofocusing points of the AAF beams can be controlled by potentials [36]. In our investigation [75], we theoretically analyzed the propagation and autofocusing effect of the AAF beams in a dynamic linear potential. We found that the linear potential may weaken (even eliminate) or strengthen the autofocusing effect of the AAF beams, depending on the form of the linear potential.…”
Section: Dynamic Linear Potential Guidancementioning
confidence: 99%
“…Among multitudinous research results that are about manipulation of the Airy beam behavior, external potentials feature prominently, such as the parabolic potential, [ 25–29 ] linear potential, [ 30 ] and dynamic potentials in general. [ 31,32 ]…”
Section: Introductionmentioning
confidence: 99%